2020
DOI: 10.18502/ijrm.v13i6.7287
|View full text |Cite
|
Sign up to set email alerts
|

Dual stimulation in unexpected poor responder POSEIDON classification group 1, sub–group 2a: A cross-sectional study

Abstract: Background: Poor ovarian response management is a complex and controversial issue in the field of reproductive medicine. Objective: The aim of this study was to apply double stimulation in the same cycle in unexpected poor responders in POSEIDON classification group 1, sub group 2a and compare assisted reproductive technology outcomes between luteal phase and follicular phase ovarian stimulation. Materials and Methods: In this cross-sectional study, 10 women with age < 35 yr, antral foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Therefore, each follicular wave may show fluctuations in antral follicle count, and COS outcome may change cycle by cycle. Eftekhar et al [ 21 ] studied dual stimulation in patients with uIOR. They reported that the number of collected oocytes was higher in luteal phase stimulation than the follicular phase stimulation in patients with uIOR (Respectively; mean oocyte number; 9.2 + 6.8 vs. 1.9 + 1.1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, each follicular wave may show fluctuations in antral follicle count, and COS outcome may change cycle by cycle. Eftekhar et al [ 21 ] studied dual stimulation in patients with uIOR. They reported that the number of collected oocytes was higher in luteal phase stimulation than the follicular phase stimulation in patients with uIOR (Respectively; mean oocyte number; 9.2 + 6.8 vs. 1.9 + 1.1).…”
Section: Discussionmentioning
confidence: 99%
“…From a literature review, 34 studies were published regarding the double stimulation approach in patients undergoing IVF treatment (Table 1). Among them, 23 studies used GnRH agonist trigger for final oocyte maturation in the first stimulation [3,4,5 ▪ ,7,8,10,11,14–23,24 ▪ ,25–29], six studies used hCG (3 rec-hCG and 2 u-hCG) [30–35], and five studies did not specifically distinguish the type of the trigger (GnRH-a ± hCG or hCG) [13,36–39]. GnRH agonist is the most common agent used for triggering and this tendency might depend on the putative negative effect exerted by the longer half-life of hCG on follicle growth during the subsequent LPS [18].…”
Section: Body Of Evidence Regarding Different Trigger Strategies In M...mentioning
confidence: 99%
“…13 There are meagre number of studies in literature evaluating the effects of dual triggering on IVF outcomes in various subgroups of patients such as hyper-responder, normo-responder or poor-responder women. 5,6,11,[14][15][16][17][18][19][20][21][22][23][24][25] Furthermore, studies reporting live birth rates, the ultimate goal of infertility treatment, in dually triggered women with expected normal ovarian response are even scarcer. 5,6,11,21,23,25 Therefore, current amount of evidence is not adequate to recommend or argue against the use of dual triggering particularly in women with predicted normal ovarian response.…”
mentioning
confidence: 99%